Soliton Booting Dynamics in an Ultrafast Anomalous Dispersion Fiber Laser - Hong-Jie Chen; Meng Liu; Jian Yao; Song Hu; Jian-Bo He; Ai-Ping Luo; Zhi-Chao Luo; Wen-Cheng Xu (IEEE Photonics Journal, 2018)
We reported on the soliton booting dynamics of an ultrafast fiber laser operating in an anomalous dispersion regime. Based on the advanced experimental methodologies of spatio-temporal reconstruction and dispersive Fourier transform (DFT), the soliton booting dynamics are analyzed in the time and spectral domains. The spectral interference pattern with strong intensity oscillation behavior was observed near the mode-locking transition. It was found that the spectral pattern distributions are induced by the transient structured soliton formation during the pulse shaping from the noise background. The experimental results were further verified by the theoretical simulations. The obtained results would provide a general guideline for understanding the soliton booting dynamics in the ultrafast fiber lasers, and will prove to be fruitful to the various communities interested in solitons and fiber lasers.